Adaptability and stability of biomass sorghum genotypes using GGE Biplot - Guerra, João Víctor Santos (2024)
The objective of this study was to evaluate the agronomic performance and select biomass sorghum genotypes for growing in different regions of Brazil based on adaptability and stability analysis using the GGE biplot method. The 25 genotypes evaluated were from trials of value for cultivation and use (VCU) of biomass sorghum of the Brazilian Agricultural Research Corporation (Embrapa Maize and Sorghum) Breeding Program, conducted in eight locations across Brazil (Sobral, CE; Jaguariúna and Narandiba, SP; Nova Porteirinha and Sete Lagoas, MG; Planaltina, DF; Vilhena, RO; and Terra Rica, PR) during the 2021-2022 crop season. A randomized block experimental design with three replications was used. The following traits of were subjected to joint analysis of variance: plant height, flowering, and fresh and dry matter yields. The confirmation of genotype-by-environment interaction (G×E) was followed by adaptability and stability analysis using the GGE biplot method for all traits. The adjusted means were used to obtain the mean clustering using the Scott-Knott test (p < 0.05). Biomass sorghum genotypes showed a longer growth cycle, taller plants, and higher biomass yield than forage sorghum genotypes. The experimental sorghum hybrids 202129B014 and 202129B016 and the commercial hybrid BRS 716 can be recommended for fresh and dry matter production in all tested environments due to their high adaptability and stability.